Pemanfaatan Bahan Pustaka dan Waktu Kunjungan Bagi Peserta Didik di Perpustakaan SD Negeri 29 Dadok Tunggul Hitam Padang - Boy Gren; Ardoni Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
Writing paper aims to find and describe: (1) benefits students after reading the materials collection at the Library of Elementary School No. 29 Dadok Black Stubble, and (2) comparison of time it takes students to the time available to visit the SD State Library Number 29 Dadok black stumps. The method used in this study is observation and interviews. Observations and interviews were conducted with stakeholders. Based on the research found that: (1) students utilize library materials in the Library of Elementary School No. 29 Black Dadok stumps to find a school assignment given by the teacher in the classroom and study bidag students to the school library just to find textbooks that are tasked by the teacher, (2) learners in elementary school No. 29 Dadok Black stumps using the breaks to visit the school library, these students expressed the schedule time available to rest like shopping, playing, resulting in a lack of interest and willingness of participants students to visit the school library. In order to use library materials can be used optimally, should Libraries Elementary School No. 29 Dadok stumps Black design a good planning before the addition of library materials. The plan includes: (1) pay attention to the needs of information desired by the student participants who will surely be used later, (2) pay attention to the age and grade level of students in accordance with the latest curriculum, (3) school institutions should provide library materials order form for learners. So that the time spent by students to visit the school library effectively, should the Elementary School Library No. 29 Dadok Black stumps have library staff who are experts in the field of libraries, so that the service schedule can be given to students to be effective. Keywords: services schedule; utilize of library collection